2017
DOI: 10.1016/j.bjm.2016.10.020
|View full text |Cite
|
Sign up to set email alerts
|

Draft genome sequence of a multidrug-resistant beta-lactamase OXA-357-producing Acinetobacter pittii ST865 clinical isolate from China

Abstract: Worldwide increasing emergence of carbapenem-resistant Acinetobacter spp. has rendered the limited availability of effective antimicrobial agents and has become a major public health concern. In this study, we report the draft genome sequence of A. pittii TCM156, a multidrug-resistant isolate that harbored the blaOXA-357 gene. The genome sequence was further analyzed by various bioinformatics methods. The genome size was estimated to be 3,807,313 bp with 3508 predicted coding regions and G + C content is 38.7%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Whole-genome sequences of A. pittii have been reported in ST119, ST207 (strain TCM292), ST220 (strain YB-45), ST865 (strain TCM156), and several strains deposited in GenBank [ 44 , 53 , 56 , 57 ]. Whole-genome SNP phylogeny revealed that our XDRAP isolates showed that the A436 (ST63) isolate was closely related to the strain WCHAP100020 from China.…”
Section: Discussionmentioning
confidence: 99%
“…Whole-genome sequences of A. pittii have been reported in ST119, ST207 (strain TCM292), ST220 (strain YB-45), ST865 (strain TCM156), and several strains deposited in GenBank [ 44 , 53 , 56 , 57 ]. Whole-genome SNP phylogeny revealed that our XDRAP isolates showed that the A436 (ST63) isolate was closely related to the strain WCHAP100020 from China.…”
Section: Discussionmentioning
confidence: 99%